Regenerative Almond Production Systems Improve Soil Health, Biodiversity, and Profit - Fenster, Tommy L. D.; Oikawa, Patricia Y.; Lundgren, Jonathan G. (Frontiers in Sustainable Food Systems, 2021)
Regenerative agriculture aims to improve soil health and promote biodiversity while producing nutritious food profitably. Almonds are the dominant crop in California agriculture in terms of acreage and revenue generated. We examined the soil health, biodiversity, yield, and profit of regenerative and conventional almond production systems that represented farmer-derived best management practices. Regenerative practices included abandoning some or all synthetic agrichemicals, planting perennial ground covers, integrating livestock, maintaining non-crop habitat, and using composts and compost teas. Total soil carbon (TSC), soil organic matter (SOM), total soil nitrogen (TSN), total soil phosphorous, calcium, sulfur, and soil health test scores were all significantly greater in regenerative soils. Water infiltrated regenerative soils six-fold faster than conventional soils. Total microbial biomass, total bacterial biomass, Gram+ bacteria, and Actinobacteria were significantly greater in regenerative soils. There was more plant biomass, species diversity, and percent cover in regenerative orchards. Invertebrate richness and diversity, and earthworm abundance and biomass were significantly greater in regenerative orchards. Pest populations, yields, and nutrient density of the almonds were similar in the two systems. Profit was twice as high in the regenerative orchards relative to their conventional counterparts. No one practice was responsible for the success of regenerative farms; their success was the result of simultaneously combining multiple regenerative practices into a single, functional farm system. This style of farming may assist in combatting planetary scale problems (e.g., climate change, biodiversity loss, agricultural pollution, chronic human health problems, and declining rural communities) while making farms more profitable and resilient.